Overview of RFID Middleware - Chrobak, Paweł (Przegląd platform RFID middleware, 2010)
In this article, the RFID middleware is introduced and compared. The overview is based on data extracted from the Forrest Research Inc. and some other sources. Main vendors of RFID middleware software was describing: IBM, Microsoft, SAP, Sun and others. In the article was also a comparison of software for applied technology, databases etc. Therefore, the basic concepts related to the RFID technology and the EPC standard are detailed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 73-86
Keywords: RFID; RFID middleware; RFID Vendors; EPC